2006
DOI: 10.1111/j.1468-2508.2006.00404.x
|View full text |Cite
|
Sign up to set email alerts
|

Corruption and Trust: Exceptionalism in Asian Democracies?

Abstract: While voluminous studies have attributed the continuing decline of institutional trust to political corruption, the link between corruption and institutional trust in Asia has yet to be explored systematically. Testing the effect of corruption on institutional trust is theoretically important and empirically challenging, since many suggest that contextual factors in Asia, such as political culture and electoral politics, might neutralize the negative impact of corruption. Utilizing data from the East Asia Baro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
248
0
9

Year Published

2007
2007
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 358 publications
(278 citation statements)
references
References 27 publications
7
248
0
9
Order By: Relevance
“…As Treisman (2000) stated, regardless of the accuracy of perceived corruption, it could exert consequences as serious as the corruption itself. For example, corruption perception erodes institutional trust (Chang & Chu, 2006;Morris & Klesner, 2010). The current results imply that politicians need to pay attention to environmental problems if they want to increase in the public's trust in them.…”
Section: Figurementioning
confidence: 75%
“…As Treisman (2000) stated, regardless of the accuracy of perceived corruption, it could exert consequences as serious as the corruption itself. For example, corruption perception erodes institutional trust (Chang & Chu, 2006;Morris & Klesner, 2010). The current results imply that politicians need to pay attention to environmental problems if they want to increase in the public's trust in them.…”
Section: Figurementioning
confidence: 75%
“…Results of several studies suggest that citizens' perception of economic and political performance is highly associated with their trust in government (Mishler & Rose, 2001;Newton, 1999;Orren, 1997). In Japan, the Philippines, South Korea, Taiwan, Kim, Public and Thailand, Chang and Chu (2006) demonstrated that the level of citizens' perception of corruption is inversely related to their trust in government institutions. Scholars in the public administration field have also emphasized that citizen participation leads to enhanced compromise, cooperation, and consideration of diverse policy options, as well as increased legitimacy of the decision-making process and deliberative democracy (Andrain & Smith, 2006;Nelson & Wright, 1995).…”
Section: Public Trust In Governmentmentioning
confidence: 99%
“…Chang dan Chu (2006); Morris dan Klesner (2010) juga menggambarkan bahwa kepercayaan ini berkaitan dengan pandangan akan kapabilitas pemerintah di dalam memenuhi apa yang masyarakat butuhkan dan inginkan. Hal tersebut tidak terlepas dari pemahaman di masyarakat bahwa korupsi hanya mengarahkan pada konteks ketidakadilan dan ketidaksetaraan (Chang & Chu, 2006). Ketika korupsi banyak merajalela pada tingkat elit politik, maka kekuasaan yang dimiliki hanya memberikan manfaat dan kemudahan bagi para diri sendiri maupun kelompoknya.…”
Section: Diskusiunclassified